Nuclear decommissioning after the German nuclear phase-out: An integrated view on new regulations and nuclear logistics - Tim Scherwath; Ben Wealer; Roman Mendelevitch (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
With Germany's nuclear phase-out, 23 reactors need to be dismantled in the near future. Initiated by the dire financial situation of the affected utilities in 2014, a major discourse on ensuring financial liability led to a redistribution of liabilities and finances, with the utilities remaining in charge of dismantling, while liability for interim and final storage now transferred to the public. This paper assesses whether the new regulation will ultimately be to the benefit of the public. It introduces a two-stage stochastic optimization framework which encompasses the different dismantling phases and resulting waste flows and storage levels of low- and intermediate-level waste (LLW and ILW) as well as the associated costs. Results show that storage risk - proclaimed as a major barrier to efficient decommissioning - is not a major driver for the optimal decommissioning schedule. However, a delay of ten years might now increase interim storage costs borne by the public by over 20%. By contrast, lacking knowledge and limited machinery is a major unaccounted cost driver, which might quickly eat-up the buffer currently included in utility funds in order to deal with dismantling uncertainties. Our analysis reveals the storage gate as the new crucial interface between utilities and the public storage provider.
Keywords: C61; H44; L51; 330; nuclear decommissioning; nuclear dismantling; financial liability; nuclear logistics; stochastic modeling; regulation